Fat-Free Mass Changes During Ketogenic Diets and the Potential Role of Resistance Training - Tinsley, Grant M; Willoughby, Darryn S (International journal of sport nutrition and exercise metabolism, 2016)
Low-carbohydrate and very-low-carbohydrate diets are often used as weight-loss strategies by exercising individuals and athletes. Very-low-carbohydrate diets can lead to a state of ketosis, in which the concentration of blood ketones (acetoacetate, 3-β-hydroxybutyrate, and acetone) increases as a result of increased fatty acid breakdown and activity of ketogenic enzymes. A potential concern of these ketogenic diets, as with other weight-loss diets, is the potential loss of fat-free mass (e.g., skeletal muscle). On examination of the literature, the majority of studies report decreases in fat-free mass in individuals following a ketogenic diet. However, some confounding factors exist, such as the use of aggressive weight-loss diets and potential concerns with fat-free mass measurement. A limited number of studies have examined combining resistance training with ketogenic diets, and further research is needed to determine whether resistance training can effectively slow or stop the loss of fat-free mass typically seen in individuals following a ketogenic diet. Mechanisms underlying the effects of a ketogenic diet on fat-free mass and the results of implementing exercise interventions in combination with this diet should also be examined.